PELATIHAN MEDIA PEMBELAJARAN ONLINE BAGI GURU DI SMA NEGERI 3 FATULEU SEBAGAI ALTERNATIF PEMBELAJARAN DI MASA PANDEMI COVID-19 - Theodora Sarlotha Nirmala Manu; Fransina Th. Nomleni; Anggreini D.N. Rupidara; Agus Maramba Meha; Yanti Daud (Yayasan Education and Social Center, 2022)
The Covid-19 pandemic, which has lasted more than a year, has had an impact on various aspects of life. One of them is in the learning process at school. SMA Negeri 3 Fatuleu also experienced various problems in the learning process during the covid-19 pandemic including: (a) teachers do not yet have the ability to use online media optimally; (b) the limited use of online learning media at SMA Negeri 3 Fatuleu; (c) Students do not understand the material due to the lack of use of online learning media that is attractive and easily accessible to students. The purpose of this service activity is to provide training on how to create various online learning media. This PKM uses the presentation method, demonstration method and practical method. PKM involved 20 teachers from SMA Negeri 3 Fatuleu. Based on the results of the questionnaire, it showed that there was an increase in the ability of teachers to use online learning media. 50% of teachers gave a very good response in understanding the material for using zoom and google meet. 60% of the teachers said they were very good at understanding the material for making E-books, 50% said they were very good at understanding the Google Form material and 50% of the teachers said they were very good at understanding the audiovisual-based mind mapping material. In addition, based on the questionnaire, as many as 65% of teachers stated that they were very good at understanding and applying the training materials while 35% said they were good in understanding and applying the training materials